Association of TNF-α gene promoter polymorphism with primary open-angle glaucoma - A.V. Shevchenko; V.F. Prokof’ev; V.I. Konenkov; A.V. Eremina; A.N. Trunov; V.V. Chernykh (РМЖ "Клиническая офтальмология")
A.V. Shevchenko1, V.F. Prokof’ev1, V.I. Konenkov1, A.V. Eremina2, A.N. Trunov2, V.V. Chernykh2 1 Research Institute of Clinical and Experimetal Lymphology — Branch of the Federal Research Center Institute of Cytology and Genetics of the Siberian Branch of the RAS, Novosibirsk, Russian Federation 2Novosibirsk Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Novosibirsk,  Russian Federation Background: glaucoma is one of the leading causes of blindness worldwide. Diagnosis of glaucoma at an early stage is challenging. Therefore, genetic factors predisposing to the development of primary open-angle glaucoma (POAG) are investigated. One of these predictors is tumor necrosis factor α (TNFα), a multifunctional proinflammatory cytokine involved in glaucoma pathogenesis. Point mutations in the regulatory region of the TNFα gene are hypothesized to be associated with POAG risk. Aim: to analyze the polymorphism of three positions of TNFα gene promoters and their complexes in West Siberian Caucasians with POAG and healthy volunteers. Patients and Methods: the study enrolled 401 individuals, i.e., 99 patients with POAG stage 2 and 302 individuals without POAG (randomized control group). All participants signed an informed consent form. Single nucleotide TNFα gene promoter polymorphism (rs361525, rs1800629, rs1800630) was analyzed. Genotyping was performed by restriction analysis of gene amplification products. Results: the occurrence of minor genotype TNF-308*АА was significantly higher in POAG (odds ratio 11.41, p=0.0011). The occurrence of two other genotypes demonstrated no significant differences between groups. Three complex genotypes were positively associated with POAG (TNF-863*CC:TNF-308*AA, TNF-308*AA:TNF-238*GG и TNF-863*CC:TNF-308*AA:TNF-238*GG). We failed to identify any single nucleotide polymorphism or complexes negatively associated with POAG. Conclusion: minor genotype TNF-308*АА is an essential factor of POAG pathogenesis. Two other polymorphic gene variants were associated with POAG as a part of complex genotypes. These findings demonstrate that potential polymorphic associations should be considered in the case-control analysis. Keywords: primary open-angle glaucoma, polymorphism, TNFα gene, gene promoter, complex genotypes. For citation: Shevchenko A.V., Prokof’ev V.F., Konenkov V.I. et al. Association of TNF-α gene promoter polymorphism with primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2022;22(1):11–15 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-11-15.